Privatization Framework: Political Economy Perspective - Indra Bastian (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2006)
Privatization has been recognized as a worldwide phenomenon. In this pa-per, a political economy approach is developed to analyze privatization. The ap-proach assumes that political economy and privatization overlap in people’s need. So, the framework of political economy in privatization is based on the ‘need’ phi-losophy. Government and private sectors are contrasted in this respect, leading to a conclusion on privatization as a method to manage the economy. Keywords: privatization, political economy, public sector accounting, public pri-vate partnership.